An Enhanced Double-layered P2P System for the Reliability in Dynamic Mobile Environments - Kim, Ji Hoon; Song, Jin Woo; Kim, Taek Hun; Yang, Sung Bong (Computing and Informatics, 2012)
The double-layered peer-to-peer (P2P) systems were introduced to reduce the network traffic in MANET. The peers in the systems are classified into super peers and sub-peers. Super peers manage their neighboring sub-peers. The network communications in the systems are done mostly among super peers. In case when a pair of neighboring super peers is too far to communicate, one or two of their sub-peers bridges the super peers. However, the double-layered systems need to improve the reliability that guarantees communications among peers. In this paper, we propose a new double-layered P2P system in which super peers are selected based on their mobility. We also propose two reliability improvement schemes, the avoidance scheme and the role changing scheme. They are applied to the proposed system to enhance the reliability of the system. The proposed system is implemented in the dynamic mobile P2P environment where peers may join and leave the network dynamically and the number of peers varies. The various experiments are done with the Network Simulator-2 v2.33. The experimental results show that the proposed system with the two schemes improved the reliability over other double-layered systems in terms of the failure rate by up to 25 %, while increasing the network traffic marginally.